Electrical properties of Al–ZrMgMo3O12 with controllable thermal expansion. Issue 2 (March 2015) - Xiao, Xiao; Zhou, Wenjin; Liu, Xiansheng; Chao, Mingju; Li, Yucheng; Zhang, Niu; Liu, Yaming; Li, Yuxiang; Feng, Dongsheng; Liang, Erjun
Abstract: Al–ZrMgMo3 O12 composites samples were prepared by the solid state method. The crystal phase and microstructure of the composites were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD patterns show two phases of Al and ZrMgMo3 O12 . The SEM images show the microstructures of the ceramics containing particles of ZrMgMo3 O12 and blocks of Al–ZrMgMo3 O12 . The ratio of particles to blocks changed on adjusting the mass ratio of Al:ZrMgMo3 O12, consequently changing the coefficient of thermal expansion (CTE) and the electrical properties of the composites. When the mass ratio of Al:ZrMgMo3 O12 is 2:8 the CTE is 0.77×10 −6 K −1 (room temperature to 673 K), which corresponds to a near-zero thermal expansion dielectric material. For Al–ZrMgMo3 O12 composite with mass ratio of 6:4, the CTE (8.72×10 −6 K −1 ) is reduced to one-third of that of Al (23.79×10 −6 K −1 ) and the impedance is decreased to 7.68 Ω. The conductivity change of Al–ZrMgMo3 O12 composites can be attributed to the conductive percolation phenomenon, resulting from the presence of large mixed blocks of Al–ZrMgMo3 O12 among the particles of ZrMgMo3 O12 .